Defence economics : achievements and challenges - Hartley, Keith (Cambridge : Cambridge University Press, 2020)
This Element introduces students, policy-makers, politicians, governments and business-people to this new discipline within economics. It presents the recent history of the subject and its range of coverage. Traditional topics covered include models of arms races, alliances, procurement and contracting, as well as personnel policies, industrial policies and disarmament. Newer areas covered include terrorism and the economics of war and conflict. A non-technical approach is used and the material will be accessible to both economists and general readers.
Title from publisher's bibliographic system (viewed on 10 Aug 2020).
Keywords: elektronické knihy; electronic books; Military readiness -- Economic aspects; Disarmament -- Economic aspects